KEMAMPUAN DAYA HAMBAT EKSTRAK BUAH MENGKUDU (Morinda citrifolia) TERHADAP BAKTERI Shigella dysenteriae - Novianti, Dewi (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2015)
ABSTRACTÂ Shigella dysenteriae an intestinal microflora in the human body that can cause diarrheal disease shigellosis or dysentery . The purpose of this study was to determine the ability of inhibitory noni fruit extract on the growth of bacteria Shigella dysenterie performed in vitro. The research was conducted in March 2015. The experimental research has been conducted on the manufacture of noni fruit extract, the extract concentration manufacture, and testing of the extract of the test bacteria. The results showed that the noni fruit extract has inhibitory effect on the growth of bacteria Shigella dysenteriae. At a concentration of 10% noni fruit extract was able to inhibit the growth of bacteria Shigella dysenteriae, and at a concentration of 80% obtained the highest inhibition zone. The higher concentration of noni fruit extract is given the greater the inhibition zone is formed. Keywords: inhibition, noni fruit extract, growth, Shigella dysenteriae